Human resource management - Durai, Pravin (Pearson : Dorling Kindersley (India), 2010)
Human Resource Management presents multifaceted and all-inclusive information that will be useful to students of human resource management as well as practising human resource managers. Using a highly readable style and real-life examples from Indian organizations, the reader becomes conversant with the latest trends as well as the basics of the theory of human resource management.